Dynamics and Control of a Four-Bar Mechanism with Relative Longitudinal Vibration of the Coupler Link - Nguyen, Van Khang; Nguyen, Sy Nam (Old Journal, 2017)
In the mechanisms and machines operating at high speeds, the elastic vibration of links is inevitable. In this paper the dynamic modeling and controller design for a flexible four-bar mechanism are studied. The fully coupled non-linear equations of motion are obtained by using the Lagrange’s equations with multipliers for constrained multibody systems. The resulting differential-algebraic equations are solved using numerical methods. A simple PD controller is designed to reduce the influence of the elastic link on the desired motion.